Meeting re Asturian miners' orphans, etc. : inter-departmental correspondence - Bolton, W. J.
030-0133-001 I.C.3. TRADES UNION CONGRESS. INTER-DEPARTMENTAL CORRESPONDENCE. From W. J. BOLTON Department International To Miss F. E. MacDONALD Date 29th June, 1938. SUBJECT. MEETING re ASTURIAN MINERS' ORPHANS, etc. Phoned Schevenels. He replies that he will be in Brussels on Tuesday morning, but could take a 'plane reaching here to attend a meeting in the afternoon. Must leave then to catch 'plane at 6 o'clock. We have promised to 'phone again. First 'plane 12.40 Croydon 210 255 292/946/30/133